2019
DOI: 10.1021/acs.jproteome.9b00363
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Non-targeted and Targeted Metabolomics Uncovers Dynamic Metabolic Effects during Short-Term Abstinence in Methamphetamine Self-Administering Rats

Abstract: Persistent neurochemical disturbances by repeating drug reward and withdrawal lead to addiction. Particularly, drug withdrawal, usually starting within hours of the last dose, is considered as a critical step in the transition to addiction and a treatment clue. The aim of this study was to uncover metabolic effects associated with methamphetamine (MA) short-term abstinence using both non-targeted and targeted metabolomics. Metabolic alterations were investigated in rat plasma collected immediately after 16 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 49 publications
6
22
0
Order By: Relevance
“…Only a few studies on amino acid profiling related to MA exposure have been conducted. In a previous study, dynamic changes were observed in the biosynthesis/metabolism of amino acids, including the phenylalanine, tyrosine, and tryptophan biosynthesis and the valine, leucine, and isoleucine biosynthesis, during 24 h of short-term abstinence in plasma from MA self-administering rats [ 48 ]. In another previous study, administration of a single dose (10 mg/kg) or escalating doses (10–30 mg/kg) of MA for five consecutive days in rats was followed by withdrawal for two days, after which 20 amino acids were profiled in the rat serum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only a few studies on amino acid profiling related to MA exposure have been conducted. In a previous study, dynamic changes were observed in the biosynthesis/metabolism of amino acids, including the phenylalanine, tyrosine, and tryptophan biosynthesis and the valine, leucine, and isoleucine biosynthesis, during 24 h of short-term abstinence in plasma from MA self-administering rats [ 48 ]. In another previous study, administration of a single dose (10 mg/kg) or escalating doses (10–30 mg/kg) of MA for five consecutive days in rats was followed by withdrawal for two days, after which 20 amino acids were profiled in the rat serum.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, all three among the seven SM were upregulated, and sphinganine, a precursor of ceramide, which is converted into a variety of sphingolipids, was down-regulated as shown in the results from the untargeted metabolomics. The dysregulation of membrane lipids, such as glycerophospholipids and sphingolipids, due to psychostimulants, such as MA and cocaine, have been previously demonstrated in human and animal studies [ 48 , 49 , 50 , 51 , 52 ]. However, the changes in these studies varied depending on the chemical nature of these lipids, sampling sites such as subparts of the brain [ 49 , 50 ], and sampling time [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the maximum number of metabolites possible, non-selective approaches have been adopted for sample preparation and instrumental analysis [2,4]. In particular, metabolomics is currently being used to identify endogenous metabolites generated after exposure to addictive drugs [8][9][10][11]. This metabolomics approach can provide a new foundation for identifying effective diagnostic markers or therapeutic targets, if the knowledge of the mechanisms of a drug's pharmacodynamic or pharmacokinetic properties is limited [12].…”
Section: Introductionmentioning
confidence: 99%